Electromagnetically induced grating via coherently driven the n-doped In0.47Ga0.53As semiconductor quantum well nanostructure. (June 2016) - Naseri, Tayebeh
Abstract: A new scheme for investigating electromagnetically induced grating (EIG) in the vanishing two-photon absorption condition in a three-level ladder-configuration n -doped semiconductor quantum well is presented. By applying a standing-wave field interacting with the system, the absorption and dispersion of the probe field will change with the spatial periodical modulation. It is shown that the first-order diffraction intensity sensitively depends on the intensity of coupling fields, detuning of applied laser fields and interaction length. Moreover, it can reach its maximum on varying the system parameters. A novel result shows the considerable efficiency of higher order diffractions is significantly improved via relative phase between applied laser fields. Furthermore, it is found that the intensity of the switching and coupling fields can increase the efficiency of the phase grating in the present model. Such a unique feature of the cooperative Electromagnetic Induced Grating may be extended to further develop diffraction based new photonic devices in quantum information networks and new photonic devices in all-optical switching and optical imaging. Highlights: A new scheme for investigating the EIG in a three-level ladder-configuration n-doped in 0.47Ga0.53As semiconductor quantum well is presented. It is shown that the first-order diffraction intensity sensitively depends on the intensity of coupling fields, detuning of applied laser fields and interaction length. A very novel result shows the considerable efficiency of higher order diffractions is significantly improved via relative phase between applied laser fields. It is found that the intensity of the switching and coupling fields can increase the efficiency of the phase grating in the present model. The present model may be instructive to design new photonic devices in optical switching and imaging